Promotional effect of iron oxide on the catalytic properties of Fe–MnOx/TiO2 (anatase) catalysts for the SCR reaction at low temperatures. Issue 6 (30th October 2015) - Deng, Shengcai; Zhuang, Ke; Xu, Bolian; Ding, Yuanhua; Yu, Lei; Fan, Yining
Abstract : The surface interaction of the iron-improved MnO x /TiO2 (anatase) catalyst for the selective catalytic reduction of nitric oxide was studied. The role of iron was investigated through detailed experiments. Abstract : The surface interaction of an iron-improved MnO x /TiO2 (anatase) catalyst for the selective catalytic reduction of nitric oxide was studied through detailed experiments. It was found that iron improved the catalyst by regulating the degree of polymerization and the dispersion of Mn oxide species supported on the anatase surface, which was the key factor for both the SCR activity and the N2 selectivity. The increased NO conversion was caused by the higher Mn oxide dispersion, while selectivity evaluation showed that N2 O formation on the MnO x /TiO2 catalyst was much higher than that on the iron-improved catalyst. Isotopic labelling experiments using 15 NH3 with NO indicated that NH was the key species for N2 O generation. NH was easily generated on MnO x /TiO2 without iron, which had a higher oxidability than the iron-improved catalyst, as identified by H2 temperature-programmed reduction experiments.